Use of three‐dimensional ultrasound imaging in the diagnosis of prenatal‐onset skeletal dysplasias - Deborah Krakow; John Williams; M. Poehl; David L. Rimoin; Lawrence D. Platt (2003)
Abstract Objective Recognition of prenatal‐onset skeletal dysplasias has improved with advances in ultrasound imaging. Skeletal abnormalities can be recognized by two‐dimensional (2D) ultrasound, but generating a precise diagnosis can be challenging. We aimed to determine whether three‐dimensional (3D) imaging conferred any advantages over 2D imaging in these cases. Methods We studied five women with fetuses of 16–28 gestational weeks referred for abnormal ultrasound skeletal findings. First 2D and then 3D sonography was performed and the results compared. Results The pregnancies resulted in the following skeletal dysplasias: thanatophoric dysplasia, achondrogenesis II/hypochondrogenesis, achondroplasia, chondrodysplasia punctata (rhizomelic form) and Apert's syndrome. For all five fetuses, the correct diagnosis was made in the prenatal period by analysis of the 2D images. In each case the 3D images confirmed the preliminary diagnosis and for many findings it improved the visualization of the abnormalities. Conclusion The 3D imaging had advantages over the 2D imaging when it came to evaluation of facial dysmorphism, relative proportion of the appendicular skeletal elements and the hands and feet. Most importantly, the patient and referring physician appreciated the 3D images of the abnormal findings more readily which aided in counseling and management of the pregnancy. Copyright © 2003 ISUOG. Published by John Wiley & Sons, Ltd.